Congenital aortic stenosis in a 40 day-old infant - İkizler, Coşkun; Saylam, Argun; Olga, Rüstem; Köşker, Seyit; Tuncalı, Tahsin; Bilgiç, Arman; Aytaç, Aydın (The Turkish Journal of Pediatrics, 1980)
The case of a 40 day-old baby girl with severe congenital valvular aortic stenosis who was subjected to open heart surgery using heart-lung machine is presented. The patient had two episodes of cardiac arrest during the preoperative period and was resuscitated. She did well during her postoperative course and was discharged in good condition. Clinical examination one year after the discharge was satisfactory. Congenital aortic stenosis and related problems are briefly discussed.